119k views
3 votes
For f(x)=3x-4 and g(x)=4x^2-3What is (g o f)(x) =?

User PhE
by
5.7k points

1 Answer

2 votes

Given:

The functions


\begin{gathered} f(x)=3x-4 \\ g(x)=4x^2-3 \end{gathered}

Required:


\text{ What is }(g\circ f)(x)?

Step-by-step explanation:

The solution steps are:


\begin{gathered} g\circ f(x)=g(f(x)) \\ g(f(x))=g(3x-4) \\ g(3x-4)=4(3x-4)^2-3 \\ =4(9x^2+16-24x)-3 \\ =36x^2+64-96x-3 \\ =36x^2-96x+61 \end{gathered}

Answer:


(g\circ f)(x)=36x^2-96x+61

User Difurious
by
4.9k points